Synthesis O-g-C3N4/TiO2 rutile composite material for photocatalytic application - M. E. Bondarenko; P. M. Silenko; Yu. M. Solonin; N. I. Gubareni; O. Yu. Khyzhun; N. Yu. Ostapovskaya (Хімія, фізика та технологія поверхні, 2019)
The development of novel materials ensuring the use of solar radiation as an inexhaustible source of renewable and environmentally friendly energy is one of the actual problems of materials science. Scientific research towards of solving this important task showed the expediency of using photocatalytic processes with the participation of semiconductor systems. One of the most well-known catalyst titanium dioxide TiO2 has photoactivity only in the ultraviolet region of the spectrum that significantly restricts its use. The application of based on undoped graphite-like carbon nitride g-C3N4 or g-C3N4/TiO2 composite catalysts allows using only part of the visible spectrum of solar radiation (with a wavelength of less than 460 nm). It is found that the doping of carbon nitride by oxygen significantly improves its photocatalytic properties to enhancing solar energy utilization. Therefore, to improve the photocatalytic activity of semiconductor photocatalyst, the coupling O-doped g-C3N4 (O-g-C3N4) with rutile TiO2 is a good strategy. Novel composite material O-g-C3N4/TiO2 was synthesized by gas phase method of deposition of        O-doped g-C3N4 on particles of rutile powder under the special reactionary conditions of the pyrolysis of melamine. Obtaining O-g-C3N4/TiO2 binary composite was confirmed through various analytical techniques including X-ray powder diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), X-ray photoelectron spectroscopy (XPS) and ultraviolet-visible diffuse reflectance spectra (UV-Vis-DRS) methods. It is found that the absorption spectra of the O-g-C3N4/TiO2 powders show a bathochromic shift of the long-wavelength edge of the fundamental absorption band (to 600 nm) relative to the absorption band of g-C3N4/TiO2 (~ 460 nm). As a result, O-g-C3N4/TiO2 photosensitivity is observed in the significant part of the visible region and the band gap of synthesized product is determined to be less than 2.4 eV versus 2.7 eV for undoped g-C3N4 or g-C3N4/TiO2. One stage constructing heterojunction structure of O-g-C3N4/TiO2 composite may be used as a low-cost way to avoid the limitations of each component and realize a synergic effect in promoting the efficient generation and separation of charge carriers, thus boosting the photocatalytic activity to enhancing solar energy utilization.